2014
DOI: 10.1016/j.jcat.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Efficient hierarchically structured composites containing cobalt catalyst for clean synthetic fuel production from Fischer–Tropsch synthesis

Abstract: Co zero field NMR a b s t r a c tWe report a straightforward preparation method to synthesize hierarchical composite consisting of TiO 2coated multi-walled carbon nanotubes (CNTs) decorating a macroscopic host structure of a-Al 2 O 3 . The obtained composite possesses moderate specific surface area and very open porous structure, as well as moderate interaction with active sites, which significantly improve the cobalt nanoparticles dispersion and the mass diffusion during the reaction. The Co/TiO 2 /CNT-a-Al 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 71 publications
3
27
0
Order By: Relevance
“…Macroporosity of catalyst improves the CO transport rate from the gas phase to the active sites through the liquid hydrocarbons filling the catalyst pores. The benefits of macroporosity incorporation into other supports for FTS catalysts (ZrO 2 , SiO 2 , CNTs, nanofibrous alumina) have been previously observed by other authors [16,[24][25][26].…”
Section: Fischer-trospch Synthesissupporting
confidence: 62%
See 1 more Smart Citation
“…Macroporosity of catalyst improves the CO transport rate from the gas phase to the active sites through the liquid hydrocarbons filling the catalyst pores. The benefits of macroporosity incorporation into other supports for FTS catalysts (ZrO 2 , SiO 2 , CNTs, nanofibrous alumina) have been previously observed by other authors [16,[24][25][26].…”
Section: Fischer-trospch Synthesissupporting
confidence: 62%
“…Recently, Liu et al [24] have developed a new hierarchical composite support of TiO 2 -coated carbon nanotubes (CNTs) grown over a-Al 2 O 3 . They indicated that this support considerably improves transport properties of reactants and products achieving FTS rates of 0.80 g C5?…”
Section: Introductionmentioning
confidence: 99%
“…Interest in this kind of materials is growing rapidly in recent years due to their intriguing characteristics in various applications including catalysis [1,2], sensors [3], adsorption [4], and energy conversion and storage [5,6]. In particular, the performance of hierarchically porous metal oxides in catalysis/photocatalysis is expected to be greatly improved over that of their counterparts with only one type of porosity [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] These carbon sources provide alternative non-crude-oil routes for the synthesis of petrol, diesel and chemicals. FT synthesis thus continues to receive attention from researchers, which has led to many technical advances in the FT process.…”
Section: Introductionmentioning
confidence: 99%